2019
DOI: 10.1016/j.jvscit.2019.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Management of celiac trunk and superior mesenteric artery synchronous aneurysms as an extremely rare manifestation of Wegener granulomatosis

Abstract: Large-vessel aneurysm is an extremely rare complication of Wegener granulomatosis. We report a case of Wegener granulomatosis in a 49-year-old woman with large synchronous aneurysms of the celiac trunk (54 mm) and superior mesenteric artery (42 mm) who presented with abdominal pain. Because of the large diameter of the aneurysms and their proximity to each other, a combination of endovascular and hybrid repair was used for management. After surgical debranching and endovascular repair, the patient was discharg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Inflammation is an immune system reaction to harmful factors that account for the induction of several cellular signals. Excessive generation of various pro-inflammatory cytokines during the process worsens this response ( 74 , 75 ). Studies have demonstrated that DM can impair reproductive organs by inducing inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is an immune system reaction to harmful factors that account for the induction of several cellular signals. Excessive generation of various pro-inflammatory cytokines during the process worsens this response ( 74 , 75 ). Studies have demonstrated that DM can impair reproductive organs by inducing inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammaging refers to the chronic, low-grade inflammation that characterizes aging. There are many mechanisms suggested for inflammation, and one of the most important ones is oxidative stress [35,36]. It is proven that inflammation is one of the leading causes of aging and can play an important role in age-related disease pathogenesis [37].…”
Section: Discussionmentioning
confidence: 99%